OPTIMIZATION OF METHODS OF PREVENTION AND TREATMENT OF INFLAMMATORY PERIODONTAL DISEASES (Лучшие интеллектуальные исследования, 2025)
Periodontal is a complex of tissues that surround the tooth and ensure its fixation in the jawbones. This complex includes the gum, the periodontal ligament connecting the tooth root to the bone socket, the alveolar processes of the jawbones and the cement of the tooth root. In certain diseases, both individual periodontal tissues and their entire complex can be affected.